Clothing and Difference : Embodied Identities in Colonial and Post-Colonial Africa - Hendrickson, Hildi, 1961- (Book collections on Project MUSE., 1996)
This volume examines the dynamic relationship between the body, clothing, and identity in sub-Saharan Africa and raises questions that have previously been directed almost exclusively to a Western and urban context. Unusual in its treatment of the body surface as a critical frontier in the production and authentification of identity, Clothing and Difference shows how the body and its adornment have been used to construct and contest social and individual identities in Nigeria, Zimbabwe, Tanzania, Kenya, and other African societies during both colonial and post-colonial times. Grounded in the insights of anthropology and history and influenced by developments in cultural studies, these essays investigate the relations between the personal and the public, and between ideas about the self and those about the family, gender, and national groups. They explore the bodily and material creation of the changing identities of women, spirits, youths, ancestors, and entrepreneurs through a consideration of topics such as fashion, spirit possession, commodity exchange, hygiene, and mourning. By taking African societies as its focus, Clothing and Difference demonstrates that factors considered integral to Western social development--heterogeneity, migration, urbanization, transnational exchange, and media representation--have existed elsewhere in different configurations and with different outcomes. With significance for a wide range of fields, including gender studies, cultural studies, art history, performance studies, political science, semiotics, economics, folklore, and fashion and textile analysis/design, this work provides alternative views of the structures underpinning Western systems of commodification, postmodernism, and cultural differentiation. Contributors. Misty Bastian, Timothy Burke, Hildi Hendrickson, Deborah James, Adeline Masquelier, Elisha Renne, Johanna Schoss, Brad Weiss.